Pericardiocentesis Procedure: Anatomical Structures and Approaches - Paul. A Divia; K Subramanyam; Jacob Meera; Avadhani Ramakrishna (International Journal of Human Anatomy, 2021)
Knowledge of accurate surface anatomy is essential for safe clinical practice. Different views and opinions for clinically important surface markings exist between clinicians. Pericardiocentesis is performed as an emergency procedure in conditions aggravating cardiac tamponade. The approach of pericardiocentesis should be held by the hands of an experienced operator because of the surrounding relations. Nowadays, the introduction of imaging-guided procedures, especially echo-guided procedures, has significantly improved the safety and feasibility of pericardiocentesis and has provided the possibility of choosing the best anatomical approach among the apical, subcostal and parasternal approaches. This case report also emphasizes the importance of instillation of agitated saline as a supplementary technique while performing echo-guided pericardiocentesis in order to reduce the likelihood of cardiac chamber perforations.
Keywords: Pericardium